Sociolinguistics in England (Palgrave Macmillan UK, 2018)
This book presents an overview of sociolinguistic research in England. Showcasing developments in sociolinguistic theory, method and application, the chapters examine sociolinguistic topics on different linguistic levels and in different geographical areas across the country. Allowing the reader to engage with contemporary research in the field, each chapter is unique in the topic or geographical area explored. Topics include historical sociolinguistics, British Sign Language, lexical variation, life-span change, and variation and innovation in urban and peripheral areas; while the regions covered range from Cornwall to West Cumbria. Edited and authored by a range of international scholars, this is sure to be a key research resource for students and scholars interested in language use in England. Natalie Braber is Reader in Linguistics at Nottingham Trent University, UK. Her research interests include language variation and identity in the East Midlands, perceptions of language in the region and studies around 'pit talk', language used by coal miners. Natalie has published widely on language variation in the East Midlands. Sandra Jansen is Senior Lecturer in English Linguistics at the University of Paderborn, Germany. Her research focuses on language variation and change, with a specific interest in Cumbrian dialects and L2 varieties of English. Sandra has published several journal articles and book chapters on language changes in the far north-west of England.